Philosophical Thinking of Al-Kindi - Hayati, Nursri; Suhendra, Ade (Darul Ilmi: Jurnal Ilmu Kependidikan dan Keislaman, 2025)
This article comprehensively examines the philosophical thought of Al-Kindi, the first Muslim philosopher to seek to integrate Greek philosophy with Islamic teachings. The study highlights three main aspects of Al-Kindi’s philosophy: (1) Talfiq, the effort to harmonize religion and philosophy by affirming that both share the same ultimate goal of seeking truth; (2) metaphysics, which holds that God is the First Cause (al-ʿillah al-ūlā), the absolute Being, and the Creator of the universe from nothing (creatio ex nihilo); and (3) the concept of the soul (al-nafs), which emphasizes that the soul is spiritual, eternal, and originates from God, attaining perfection when it is liberated from the body. The Methodology used is library research with the technique of content analysis. Through his works spanning various disciplines, Al-Kindi laid the foundations for the development of a rational and religious Islamic philosophy. His perspective asserts philosophy is not a threat to religion. However, rather than being a tool for strengthening and deepening our comprehension of divine truths. His intellectual legacy became a foundation for subsequent developments in Islamic philosophical thought, including those of Al-Farabi, Ibn Sina, and Ibn Rushd